ANALISIS PENILAIAN KINERJA KEUANGAN PENDAPATAN PEMERINTAH DAERAH KABUPATEN SUBANG DENGAN MENGGUNAKAN METODE RASIO KEUANGAN - Iyak Solihat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to determine the Financial Performance Assessment Subangdistrict government by using the method of Financial Ratios. By analyzing thefinancial budget realization reports in 2015 to 2017. So the results of this studyindicate that the assessment of the subang district government's financialperformance in 2015 to 2017 can be said to be very good. This is indicated by avery good degree of decentralization with an average percentage of 100%. Verylow regional financial dependence at 0%. Regional financial independence is highwith a delegative relationship pattern, which is 100%, while the averageeffectiveness of a very effective PAD is 122.53. The average efficiency of a veryefficient PAD is 4.01%. The average effectiveness of a very effective local tax is115.48%. And the average efficiency of a very efficient local tax is 4.22..